The Influence of Influencers on the Instant Lifestyle of Middle-Class Muslims in Pontianak from the Perspective of the Theory of Planned Behavior - Rokade; Luqman; Amalia Irfani (Cv. Syntax Corporation Indonesia, 2026)
The culture of digitalization translated by humans in the influencer profession, which directly or indirectly has an impact on several aspects of people's lives. Influencer is one of the professions that quite affects the lifestyle of the middle-class Muslim community in the city of Pontianak, which is slowly changing their lifestyle toward an instant direction. For example, buying food with the GoCod application, buying goods with the Shopee application. Seen through the perspective of planned behavior theory, this qualitative research employed data collection using in-depth interview techniques, with informant determination conducted through purposive sampling strategies. The results of the study show that influencers have an influence on the instant lifestyle choices of middle-class Muslims in the city of Pontianak through digital content that they create or by serving as brand ambassadors. The phenomenon of instant lifestyle in the middle-class Muslim community in the city of Pontianak can be understood as a form of response to the digitalization phenomenon, which today makes influencers one of the public figures who most influence people's lifestyles. In addition, the instant lifestyle of the middle-class Muslim community in the city of Pontianak is a form of action that is very controlled and carried out with full awareness and without coercion.